Effect of Stratification and Gibberellic Acid on Germination and Seedling Growth of Acer acuminatum in North Western Himalayas - Kumar, Suresh; Shamet, G. S.; Gupta, Dinesh; Kumari, Neena; Kumar, Raj (Indian Forester, 2017)
The presence of physiological dormancy in Acer acuminatum (Wall. ex D. Don) seeds poses a challenge for its germination. In the present study we investigated the effect of stratification and gibberellic acid (GA3) on seed germination and seedling growth of A. acuminatum for two years. The seeds were subjected to five stratification periods of twenty day interval i.e. 0, 20, 40, 60 and 80 days; three stratification temperatures viz., room temperature, 3±1°C and -3±1°C and finally treated with distilled water and 200 ppm GA3 prior to sowing. Half of the seeds were sown in the laboratory conditions while the other half was sown in polybags in the shade net house. The results showed that the seeds subjected to 60 day stratification provided significantly maximum germination (43.61% and 38.06%) in both conditions. Similarly, 3±1°C stratification provided significantly best germinability and seedling growth. GA3(200 ppm) application also proved to enhance germination of the seeds in both conditions.